THE DEVELOPMENT OF STUDENT WORKSHEET BASED ON PROJECT BASED LEARNING TO PRACTICE BIOENTREPRENEURSHIP SKILLS ON THE TOPIC ECOSYSTEM FOR X GRADE SENIOR HIGH SCHOOL - Putri, Talitha Sandhe; Purnomo, Tarzan (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
AbstractBioentrepreneurship is one of the needed life skills nowadays. That skills can be practiced to students by applying project based learning (PjBL) model on the topic ecosystem. In ecosystem materials, one of the basic competencies (4.10.) required for students was to create work that showed interactions between ecosystem components. Through the work the students were also trained to create works that are worth selling, therefore the ability of bioentrepreneurship can be trained. Activities to practice bioentrepreneurship skills could be incorporated by applying project based learning model guided by worksheet. The purpose of this study was to: producing student worksheet of based project based learning model to practiced bioentrepreneurship skills in material ecosystem topic for grade X High School that decent theoretically and empirically. Thoretical decent based on validation. Empirical decent based on implementation, study result, and student’s respons. This research was a development, which used 4D methods consisting of define, design, develope, and dessiminate but do not disseminate stage. Student worksheet trial was conducted on twenty students of grade X High School. The assembly of data use method of validaty, observation, test, and questionnaire. The result of this research was student worksheet of based project based learning model could practice bioentrepreneurship skills to students with vailidity value that obtain 94,98% which level is very decent chategory. Empirical decent based on implementation of student worksheet is 94,88%, study result of students is 93%, students activity is 99,44%, student’s respons of students worksheet is 99%, and student’s respons on entrepreneurial interest is 89,5% which level is very good chategory.Keywords: The students’ worksheet (LKPD), Project Based Learning (PjBL) model, Bioentrepreneurship Skills, Ecosyste